Nutrition support for the critically ill patient : a guide to practice - Cresci, Gail (Taylor & Francis, 2005)
Suitable for clinicians working in a critical care setting, this work discusses ethical and economic issues for nutrition support in the ICU. It focuses on the nutritional needs of the patient, including metabolism issues, assessment, nutrient delivery, and lifecycle considerations, such as pregnancy and old age